Weak central coherence in neurodevelopmental disorders: a comparative study - Gambra, Leyre; Magallon, Sara; Crespo-Eguílaz, Nerea (Frontiers in Psychology, 2024)
Introduction Central coherence is the normal tendency to process and give meaning to incoming information taking into account the context or global view of that information. Methods We assessed the central coherence of 252 school children of normal intelligence between 6 and 11 years old. We compared the performance of two groups: (a) a control group (n = 194), and (b) a clinical group (n = 58) comprising children with NVLD+ADHD (n = 24), ADHD alone (n = 16), SCD (n = 8) and level-1ASD (n = 10) (Kluskall-Wallis H and Mann-Whitney U were calculated to make comparisons within groups and between pairs of groups). The effects of medication were studied (Student’s t test). Results The NVLD+ADHD, SCD and ASD1 groups showed weak central coherence. The performance of the ADHD group was normal and differed significantly from the NVLD+ADHD group. Conclusion Central coherence deficit was not exclusive to ASD1: it also characterizes NVLD and SCD.